A novel application of the consumer rejection threshold method to the design of binary red wine blends prepared from traditional and fungus-resistant varieties - Paire, Caroline; Cheriet, Foued; Samson, Alain; Chervin, Christian; Arino, Audrey; Ruetsch, Gabriel; Ithurralde, Estelle; Geffroy, Olivier (OENO one, 2025)
Fungus-resistant grape (FRG) varieties obtained through interspecific hybridisation, are currently seen as a credible solution for reducing the use of pesticides in viticulture. One possibility is to include wines made from FRG in blends prepared from traditional varieties. Such addition is likely to negatively affect consumer’s liking notably in red blends as red wines made from FRG may exhibit higher acidity, lower tannin content and stability given their high protein levels. This study aimed to apply the Consumer Rejection Threshold (CRT) method to determine to which extent red FRG wines can be incorporated into blends. Two red FRG wines, made from Vidoc and Artaban, were selected for the study and blended with a Merlot wine. After a first experiment consisting of identifying detection thresholds for FRG wines in a blend for untrained and expert panellists, a second experiment based on paired preference tests following the CRT method was conducted with consumers only. The detection thresholds were estimated for untrained subjects at 24.9 % v/v for Artaban, and 14.1 % v/v for Vidoc, highlighting a lower sensitivity than experts for which Artaban and Vidoc were detected at 6.9 % and 7.7 % v/v, respectively. During the second experiment, blends containing between 25 % and 60 % v/v of Artaban were less preferred than the single-variety Merlot wine but neutrally perceived over 60 % v/v. Surprisingly, Vidoc blends were neutrally perceived in comparison with Merlot for all the levels of incorporation evaluated, suggesting the existence of distinct clusters of consumers. Four groups of preferences were identified through Principal Component Analysis (PCA) and Hierarchical Agglomerative Clustering (HAC). Among these groups, only one representing 21 % of panellists, composed of a larger proportion of daily wine drinkers who identified themselves as novices in wine, showed a marked preference for Merlot over Vidoc blends. Overall, our results show the absence of a major sensory obstacle for the incorporation of the two studied FRG wines in Merlot blend which indicates a good consumer acceptability of these wines and encourages the wine industry to use FRG red wines for blending or in single cuvée.